Model of Java Traditional Games in Forming Social Character of Early Age in TK Perwanis Medan - Halimatus Sadiah; Rosmala Dewi; Evi Eviyanti (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This study aims to describe how the implementation of traditional Javanese game models in shaping the social character of children in Perwanis Medan Kindergarten as well as describing what social characters are produced from traditional Javanese games (hide and seek, congklak, crank, and cublak-cublak suweng). This research is a type of qualitative descriptive study, with research subjects namely the school principal, teacher, school committee, and several children at TK Perwanis Medan. Data collection techniques used in the form of; observation, interview and documentation. Analysis of the data used in the form of descriptive analysis, which includes three pathways namely; data reduction, data presentation, and drawing conclusions. The conclusion obtained is that the implementation of social character formation through traditional games has been going well and optimally, while the indications of each of the basic elements of social character education, including: moral knowing (moral knowledge), moral feeling (feelings about morals), and moral action ( moral action). In addition, the social character contained in every traditional Javanese game, among others: 1) Plot Umpet; honest, love peace, discipline, tolerance, hard work, curiosity, love of the motherland, and responsibility. 2) Congklak; honest, tolerance, discipline, creative, communicative, peace-loving, and responsibility. 3) Engklek; honest, discipline, love the motherland, hard work, and love peace. 4) Suweng sub-sub-groups; honest, hard work, curiosity, and love peace.